Posted by so lost on Sunday, January 30, 2011 at 8:41pm.
Divide both sides by -(2/5)
x = (6/35) / -(2/5)
x = (6/35) * -(5/2)
x = -(30/70)
x + -3/7
-2/5 x = 6/35
Multiply both sides by 35
-14x = 6
x = -6/14 = -3/7
thank you after i looked back over it I saw that I didn't break it down far enough
(x power 3)+ 14x -6=0 ????
Algebra - Solve using the multiplication principle. -4/5x=16/35. (5)-4/5x=16/35(...
algebra - solve by using multiplication principle -3/7x=6/35 x=______________
algebra - using multiplication principle -2/5y=-14/15
Algebra - Could someone please help me with this problem? Solve using the ...
Algebra - Question 1 Solve using the multiplication principle then graph. -15&...
algebra - solve using the multiplication principle: -7x > 1/15
algebra - How would you solve this using the multiplication principle? -7x&...
algebra - how would I solve using addition or multiplication principle? x+15&...
mATH - solve using multiplication principle. -2/7x=6/35
algebra - Solve using the multiplication principle. 3/4x=9/10. Would the answer ...
For Further Reading